Colonization of minds: Ukraine between Russian colonialism and Western Orientalism - Kotliuk, Galyna (Frontiers in Sociology, 2023)
This article focuses on investigating how Russian colonialism has re-invented Ukrainian identity and framed its perception both in Ukraine and in Western societies. Although postcolonial approaches to studying power hierarchies have contributed a lot to our understanding of global inequalities, Ukraine has long been excluded from this interdisciplinary complex discussion. Such an exclusion has created a gap in knowledge, which this study aims to address through the analysis of gender identities and roles evolution in Ukrainian society as well as critical rethinking of the existing body of knowledge. This article demonstrates the degree to which European societies perceived Ukrainians as Orientalized passive objects, which went in line with Russian imperialistic ideology of russkii mir, examines its influence on gender identities in Ukraine and, finally, proves that strengthening of Ukrainian civil society as well as women's and LGBTQ+ rights is a part of the decolonial processes which were instigated by the Russian war against Ukraine.